Analisis Faktor Penyebab Kesulitan Belajar Siswa Pada Pembelajaran IPS di SMP Mu'alimin Wonodadi, Blitar - Joko Dery Waluyo; Irma Yunita; Adiel Hasan Danica Hidayat; Bagus Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The objective of this study is to investigate the factors that lead to difficulties in students' social studies learning at Mu'alimin Wonodadi Junior High School in Blitar. Learning difficulties are a common problem faced by students in learning social studies (Social Studies). The factors contributing to learning difficulties are complex and varied, covering individual factors, friendship factors and environmental factors both in the school and family environment. This research method uses qualitative research where researchers directly go to the field. Researchers utilize a range of tools for data collection, such as interviews, observation, and documentation. The results highlight several key factors that contribute to students experiencing difficulties in their learning. learning social studies, including external or external factors such as factors from the environment both outside and from within the family and internal or internal factors such as interest, talent and motivation.